2006
DOI: 10.1086/508922
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Galaxy Kinematics toz∼1 in the TKRS/GOODS‐N Field. II. Evolution in the Tully‐Fisher Relation

Abstract: We use kinematic measurements of a large sample of galaxies from the Team Keck Redshift Survey in the GOODS-N field to measure evolution in the optical and near-IR Tully-Fisher (TF) relations to z ¼ 1:2. We construct TF relations with integrated line-of-sight velocity widths of $1000 galaxies in B and $670 in J; these relations have large scatter, and we derive a maximum likelihood least-squares method for fitting in the presence of scatter. The B-band TF relations, from z ¼ 0:4 to 1.2, show evolution of $1.0Y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
159
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(172 citation statements)
references
References 69 publications
12
159
1
Order By: Relevance
“…Most other observational studies also derived (or assumed) a TFR slope independent of look-back time (e.g., Bamford et al 2006;Miller et al 2011; we note that these authors also relied on an inverse fit for their analysis). Only Weiner et al (2006) reported an increased TFR slope in the range 0.4 < z < 1; however, their results are not directly comparable to ours since the approach by Weiner et al lacks corrections for disk inclination and, in turn, for the inclination-dependent optical beam smearing effect (see Sect. 4.3).…”
Section: Appendix A: Distant Tully-fisher Relation Slopecontrasting
confidence: 86%
“…Most other observational studies also derived (or assumed) a TFR slope independent of look-back time (e.g., Bamford et al 2006;Miller et al 2011; we note that these authors also relied on an inverse fit for their analysis). Only Weiner et al (2006) reported an increased TFR slope in the range 0.4 < z < 1; however, their results are not directly comparable to ours since the approach by Weiner et al lacks corrections for disk inclination and, in turn, for the inclination-dependent optical beam smearing effect (see Sect. 4.3).…”
Section: Appendix A: Distant Tully-fisher Relation Slopecontrasting
confidence: 86%
“…A galaxy undergoing a slow quench is not necessarily quiescent by the time of observation. This SFH model has previously been shown to appropriately characterise quenching galaxies (Weiner et al 2006;Martin et al 2007;Noeske et al 2007;Schawinski et al 2014). …”
Section: And Charlot 2003 Hereafter Bc03) Assumes a Chabrier Imfmentioning
confidence: 98%
“…If we apply the maximum likelihood method of Weiner et al (2006) to fit the new line-width data (i.e., all the data in the left panel of Figure 1 except those of McGaugh et al 2000), we obtain a slope x = 3.41 ± 0.08 and an intercept log A = 2.91 ± 0.17. If we perform the same exercise with the rotation curve data in the right panel of Figure 1, we obtain x = 3.94 ± 0.11 and log A = 1.81 ± 0.22.…”
Section: Comparison Of the Datamentioning
confidence: 99%